Thermal behaviour and tolerance to ionic liquid [emim]OAc in GH10 xylanase from Thermoascus aurantiacus SL16W - Niwat Chawachart (2018)
© 2014, Springer Japan. GH10 xylanase from Thermoascus aurantiacus strain SL16W (TasXyn10A) showed high stability and activity up to 70–75 °C. The enzyme’s half-lives were 101 h, 65 h, 63 min and 6 min at 60, 70, 75 and 80 °C, respectively. The melting point (Tm), as measured by DSC, was 78.5 °C, which is in line with a strong activity decrease at 75–80 °C. The biomass-dissolving ionic liquid 1-ethyl-3-methylimidazolium acetate ([emim]OAc) in 30 % concentration had a small effect on the stability of TasXyn10A; Tmdecreased by only 5 °C. It was also observed that [emim]OAc inhibited much less GH10 xylanase (TasXyn10A) than the studied GH11 xylanases. The Kmof TasXyn10A increased 3.5-fold in 15 % [emim]OAc with xylan as the substrate, whereas the approximate level of Vmaxwas not altered. The inhibition of enzyme activity by [emim]OAc was lesser at higher substrate concentrations. Therefore, high solid concentrations in industrial conditions may mitigate the inhibition of enzyme activity by ionic liquids. Molecular docking experiments indicated that the [emim] cation has major binding sites near the catalytic residues but in lower amounts in GH10 than in GH11 xylanases. Therefore, [emim] cation likely competes with the substrate when binding to the active site. The docking results indicated why the effect is lower in GH10.